The nexus of tourism spending with economic performance: A panel data analysis for the Eurozone area - Anagnostou, Ageliki; Ekonomou, George; Kallioras, Dimitris (Geographica Pannonica, 2021)
The paper investigates the nexus of tourism spending (i.e. leisure and business tourism spending) with economic performance (i.e. GDP and employment) for the Eurozone countries, during the period 2000-2018, employing sophisticated panel data analysis techniques. The issue is salient, given that within the Eurozone economic space the abolition of border impediments has released dynamics and brought into surface a new mix of opportunities, threats and challenges that has been changing the balance between centripetal and centrifugal forces. The findings of the paper identify the long-run equilibrium and confirm the bi-directional relationships among the variables considered, thus contributing to the discussion on the relationship between tourism and economic performance.